Inclusion of persons with disabilities in systems of social protection: a population-based survey and case–control study in Peru - Bernabe-Ortiz, Antonio (2016)
OBJECTIVE: This study aims to assess the needs of people with disabilities and their level of inclusion in social protection programmes. DESIGN: Population based-survey with a nested case-control study. SETTING: Morropon, a semiurban district located in Piura, northern Peru. PARTICIPANTS: For the population survey, a two-stage sampling method was undertaken using data from the most updated census available and information of each household member aged ≥5 years was collected. In the nested case-control study, only one participant, case or control, per household was included in the study. PRIMARY AND SECONDARY OUTCOME MEASURES: Disability was screened using the Washington Group short questionnaire. A case, defined as an individual aged ≥5 years with disabilities, was matched with one control without disabilities by sex and age (±5 years). Information was collected on socioeconomic status, education, health and rehabilitation and social protection participation. RESULTS: The survey included 3684 participants, 1848 (50.1%) females, mean age: 36.4 (SD: 21.7). A total of 290 participants (7.9%; 95% CI 7.0% to 8.7%) were classified as having disability. Adults with disabilities were more likely to be single (OR=3.40; 95% CI 1.54 to 7.51) and not to be working (OR=4.36; 95% CI 2.26 to 8.40), while those who did work were less likely to receive the national minimum wage (ie, 750 PEN or about US$265; p=0.007). People with disabilities were more likely to experience health problems. There was no difference between those enrolled in any social protection programme among participants with and without disabilities. CONCLUSIONS: People with disabilities were found to have higher needs for social protection, but were not more likely to be enrolled in social protection programmes. The Peruvian social protection system should consider adding disability status to selection criteria in their cash transfer programmes as well as implementing disability-specific interventions. Published by the BMJ Publishing Group Limited. For permission to use (where not already granted under a licence) please go to http://www.bmj.com/company/products-services/rights-and-licensing/